Differential prognostic accuracy of right ventricular dysfunction, the Seattle heart failure model and the MAGGIC score in patients with severe mitral regurgitation undergoing the MitraClip® procedure. (December 2020) - Heyl, S.; Luu, B.; Wieszner, M.; Nikkhoo, A.; Seeger, F.; Hemmann, K.; Assmus, B.; Kaess, B.; Zeiher, A.M.; Walther, C.; Fichtlscherer, S.; Honold, J.
Abstract: Background: MitraClip ® (MC) is an established procedure for severe mitral regurgitation (MR) in patients deemed unsuitable for surgery. Right ventricular dysfunction (RVD) is associated with a higher mortality risk. The prognostic accuracy of heart failure risk scores like the Seattle heart failure model (SHFM) and Meta-Analysis Global Group in Chronic Heart Failure (MAGGIC) score in pts undergoing MC with or without RVD has not been investigated so far. Methods: SHFM and MAGGIC score were calculated retrospectively. RVD was determined as tricuspid annular plane systolic excursion (TAPSE) ≤15 mm. Area under receiver operating curves (AUROC) of SHFM and MAGGIC were performed for one-year all-cause mortality after MC. Results: N = 103 pts with MR III° (73 ± 11 years, LVEF 37 ± 17%) underwent MC with a reduction of at least I° MR. One-year mortality was 28.2%. In Kaplan-Meier analysis, one- year mortality was significantly higher in RVD-pts (34.8% vs 2.8%, p = 0.009). Area under the Receiver Operating Characteristic (AUROC) for SHFM and MAGGIC were comparable for both scores (SHFM: 0.704, MAGGIC: 0.692). In pts without RVD, SHFM displayed a higher AUROC and therefore better diagnostic accuracy (SHFM: 0.776; MAGGIC: 0.551, p < 0.05). In pts with RVD, MAGGIC and SHFM displayed comparable AUROCs. Conclusion: RVD is an important prognostic marker in pts undergoing MC. SHFM and MAGGIC displayed adequate over-all prognostic power in these pts. Accuracy differed in pts with and without RVD, indicating higher predictive power of the SHFM score in pts without RVD.